EFFECT OF VERMICOMPOST EXTRACT AND MINERAL FERTILIZER ON GROWTH, YIELD OF BARLEY AND SOME NUTRIENTS AVAILABILITY IN THE SOIL - Haider A. Al-Maamori,; Sinan Samir Juma,; Firas W. Ahmed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
An experiment was conducted to study the effect of vermicompost extract and mineral fertilizer on growth, grain yield of barley and nutrients availability during the season 2021-2022, in clay loam soil using Randomized Complete Block design (RCBD). Vermicompost extract was added at three levels: without addition (VE0), injected into the soil (VE1) and applied as a foliar application (VE2). Mineral fertilizer was added at (0, 50 and 100%) from the recommended level Symbolized (C0, C1 and C2) sequentially. Results showed a significant effect of adding mineral fertilizer at 100% from the recommended level in available nitrogen and phosphorus in the soil achieved 32.06 mg N kg-1 and 21.55 mg P kg-1 respectively, and also excelled in plant height, leaf area, stalks number, 1000 grains weight, grain yield and biological yield) which achieved 66.36 cm and 18.45 cm2, 7.91 stalks plant-1, 41.78 g, 4.05 and 10.93 Mg ha-1 respectively. Vermicompost extract gave a significant effect as a spray on the plants compared to the injected into the soil in available nitrogen, phosphorus in the soil, stalks number, 1000 seeds weight, grain yield and biological yield which achieved 31.48 mg N kg-1, 19.72 mg P kg-1, 7.58 stalks plant-1, 39.43 g, 4.02 and 10.34 Mg ha-1 respectively.